The thrombin inhibitors hirudin and Refludan® activate the soluble guanylyl cyclase and the cGMP pathway in washed human platelets - Kobsar, Anna; Koessler, Juergen; Kehrer, Linda; Gambaryan, Stepan; Walter, Ulrich (Thrombosis and Haemostasis, 2012)
A number of direct thrombin inhibitors are successfully used clinically and experimentally as novel antithrombotics and specific anticoagulants. They are also used as anticoagulants in certain blood collection tubes for the analysis of platelet function. A series of platelet function tests have emerged to measure adequate responses to antiplatelet therapy. For comparative and practical reasons, it would be of advantage to use the same anticoagulant in blood collection tubes for different methods, e.g. thrombin inhibitors. However, there are little data on the effects of thrombin inhibitors on platelet signalling pathways that could influence results. We examined the applicability of thrombin inhibitor containing blood for platelet reactivity index (PRI) measurements of the VASP assay and investigated the effects of two thrombin inhibitors (hirudin and lepirudin) on cAMP- and cGMP-mediated signalling pathways in washed human platelets. We show that induction of VASP phosphorylation by PGE1 is markedly reduced in lepirudin containing blood samples. In consequence, PRI levels were highly variable compared to routinely used citrated blood. Surprisingly, in vitro incubation of platelets with thrombin inhibitors increases platelet cGMP levels and induces NOS independent sGC/PKG-mediated VASP phosphorylation. We conclude that thrombin inhibitors activate sGC/PKG-dependent pathways resulting in an increase of VASP phosphorylation which contributes to deviations in PRI measurements. These effects of thrombin inhibitors on sGC- and cGMP-mediated pathways including increased VASP phosphorylation may indicate the presence of an important additional platelet-based mechanism for the reduction of thrombus formation and thromboembolism by thrombin inhibitors.
Keywords: VASP; PRI; lepirudin; hirudin; sGC/ PKG/ cGMP pathway